Food Aversions in Women During The 2 Years After Roux-En-Y Gastric Bypass - Sousa Novais, Patricia Fatima [UNESP]; Rasera Junior, Irineu [UNESP]; Shiraga, Elisabete Cristina; Oliveira, Maria Rita Marques [UNESP] (Springer, 2011)
The anatomical and physiological changes of the gastrointestinal tract after Roux-en-Y gastric bypass lead to changes in dietary patterns and their effects are still little known. Hence, the objective of this work was to characterize the prevalence, the associated factors and the list of food aversions with the effect of surgery on the body weight of women in the first two years after Roux-en-Y gastric bypass. A total of 141 women were studied. Their food aversions were assessed with a short food frequency questionnaire (FFQ-S) containing 26 items before and 6, 12 and 24 months after surgery. The FFQ-S was filled out during individual interviews and referenced in the medical records. The association between total aversion score and body weight variables and general characteristics of the group was analyzed. Variation of food aversions over time was assessed for 26 foods individually and grouped. of all the studied variables, a weak but significant negative correlation (rs = -0.1944; p = 0.0208) was found between total aversion score and shorter postoperative period and a weak but significant positive correlation was found between total aversion score and percentage of weight regained (rs = -0.1759; p = 0.0369). Food aversions were more common in the first six months after surgery, especially to red meats, rice, chicken, eggs, pasta, milk and others. Food aversions in the early postoperative period are associated with weight variations in the first two years after surgery and subside significantly over time, probably because of a physiological and cognitive adaptation of the individual to the surgical procedure.
Keywords: Morbid obesity; Bariatric surgery; Food intake; Gastric bypass